Mini-Dirac cones in the band structure of a copper intercalated epitaxial graphene superlattice. (5th July 2016) - Forti, S; Stöhr, A; Zakharov, A A; Coletti, C; Emtsev, K V; Starke, U
Abstract: The electronic band structure of an epitaxial graphene superlattice, generated by intercalating a monolayer of Cu atoms, is directly imaged by angle-resolved photoelectron spectroscopy. The 3.2 nm lateral period of the superlattice is induced by a varying registry between the graphene honeycomb and the Cu atoms as imposed by the heteroepitaxial interface Cu/SiC. The carbon atoms experience a lateral potential across the supercell of an estimated value of about 65 meV. The potential leads to strong energy renormalization in the band structure of the graphene layer and the emergence of mini-Dirac cones. The mini-cones' band velocity is reduced to about half of graphene's Fermi velocity. Notably, the ordering of the interfacial Cu atoms can be reversibly blocked by mild annealing. The superlattice indeed disappears at ∼220 °C.